Penerapan Inovasi Dalam Penguatan Pasar Melalui Digital Visual Branding dan Peningkatan Produksi Sari Lemon Yoeni - Hasibuan, Annalisa Sonaria; Rezha Destiadi; Muhammad Anhar Pulungan; Andi Supriadi Chan (Jurnal Tiyasadarma, 2025)
Sari Lemon Yoeni is a lemon juice drink located in the city of Medan which is used as an ingredient in other drinks, such as coffee, tea and other drinks that are usually served in coffee shops and restaurants. However, there are several obstacles faced by partners related to production, promotion, product branding, and packaging. The purpose of this activity is to transfer knowledge and technology to partners in an effort to improve product branding, production, promotion and product packaging, which is carried out in this activity is divided into three stages. The first stage of activity preparation, the stage of implementing coaching activities and evaluating activities. Activities will be carried out until December 2024. Based on the results of visits and interactions with partners, it shows that there are several problems as described previously. So the program and solution offered to solve the problems faced by these partners is to provide expertise training in digital content usage techniques as a means of promotion and marketing of lemon products, product packaging that is in accordance with Basic Standards and needs so that it can be used for packaging sales of lemon juice production results and understanding and registration of trademarks for products so that they can be sold in North Sumatra. The steady increase in production to 60 bottles/production and repackaging of the product is better than before so that it can compete in the market, and partners understand the importance of marketing using social media and e-commerce in increasing sales of Yoeni lemon juice products.